Poplars for Farm Forestry in Uttar Pradesh - Chaturvedi, A. N. (Indian Forester, 1983)
Poplars from U.S.A. and U.K. were first tried in U.P hills during 1950. Continuous research for three decades have established that certain clones grow very well in the tarai tract of U.P. They can be commercially harvested in about 12 years initial trials have indicated that some clones may be successfully grown on usar soils viable seeds have been obtained from clones G-48, G-121 and 69/55 opening possibilities of future genetical work.